2015
DOI: 10.1021/acs.molpharmaceut.5b00466
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Residues in the Putative Transmembrane Domain 11 of Human Organic Anion Transporting Polypeptide 1B1 Dictate Transporter Substrate Binding, Stability, and Trafficking

Abstract: Organic anion transporting polypeptides (OATPs, gene symbol SLCO) are membrane proteins that mediate the sodium-independent transport of a wide range of endogenous and exogenous compounds. Due to their broad substrate specificity, wide tissue distribution, and involvement in drug-drug interactions, OATPs have been considered as key players in drug absorption, distribution, and excretion. Transmembrane domains (TMs) are crucial structural features involved in proper functions of many transporters. According to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…We confirmed that the characteristics of TCA transport ( K m values of 10.6 ± 0.3 μM and 9.5 ± 0.9 μM for OATP1B1 and OATP1B3, respectively) were similar to those of previous reports [2123, 31]. The K m values for OATP1B1- and OATP1B3-mediated uptake of bile acids in present study and previous reports are summarized in S2 Table.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We confirmed that the characteristics of TCA transport ( K m values of 10.6 ± 0.3 μM and 9.5 ± 0.9 μM for OATP1B1 and OATP1B3, respectively) were similar to those of previous reports [2123, 31]. The K m values for OATP1B1- and OATP1B3-mediated uptake of bile acids in present study and previous reports are summarized in S2 Table.…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicated that glycine and taurine conjugated bile acids and unconjugated bile acids, except for UDCA and LCA, are substrates for both OATP1B1 and OATP1B3 (Fig 2). Previous studies reported that CA, GCA, TCA, GCDCA, TCDCA, TDCA, GUDCA, and TUDCA are substrates of OATP1B1 and OATP1B3 [2227, 3135]. However, earlier studies have demonstrated that CA and TCA were not substrates for OATP1B3 [21].…”
Section: Discussionmentioning
confidence: 99%
“…A similar phenomenon was observed in our previous study of OATP1B1. It was found that several amino acid residues along TM11 are crucial for uptake function of the transporter, and they are located three and/or four residues apart from each other (Hong et al, 2015). Indeed, homology modeling (Biasini et al, 2014) of OATP2B1 (Supplemental Material) with Escherichia coli glycerol-3phosphate transporter (Protein Data Bank: 1pw4, Supplemental Material) as template revealed that V52, H55, L58, Q59, A61, Q62, S66, and L69 are all localized along one side the a-helix, facing the inner channel formed among different transmembrane domains (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified quite a few essential amino acids located within transmembrane domains of OATP members. For example, amino acid residues within TM2 (Li et al, 2012), TM6 (Huang et al, 2013), TM10 (Gui andHagenbuch, 2009;Ohnishi et al, 2014), and TM11 (Weaver and Hagenbuch, 2010;Hong et al, 2015) were shown to be crucial for proper function of OATP1B1, and TM8 (Miyagawa et al, 2009) is believed to be important for substrate recognition of the transporter. As for OATP1B3, K41 in TM1 and R580 in TM11 are believed to be pivotal to the transporter function (Glaeser et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring coding region variants of OAT4, especially L29P and T392I in TMDs 1 and 8, exhibited greatly decreased plasma membrane expression (Zhou et al, ). Alanine‐scanning mutagenesis of TMD11 in OATP1B1 identified 7 critical amino acid residues for plasma membrane expression and function (Hong et al, ). It would now be of interest to evaluate the role of the analogous residues in other OATPs to elucidate the molecular mechanisms underlying the loss of membrane expression.…”
Section: Post‐translational Processing Of Slc Transportersmentioning
confidence: 99%